Republican Dentists in Latin America: Luis Amado Blanco Fernández and his Contributions to Cuban Dentistry - Victoria María Sueiro Rodríguez; Asela Crescencia Villaurrutia Flores; Julia Roquelina Fuguet Boullón (Medisur)
The Spanish Civil War caused a mass exodus of men and women of science and letters, who went into exile stripped of their university chairs. At their arrival to the Americas, they joined the sociocultural and scientific institutions, leaving their enduring marks here. Much has been written about the literary exile; however, the scientific exile, particularly in the branch of Dentistry, has not received equal attention. Some books, monographs and papers have addressed this subject, in addition to some conferences, where scientific exile in Cuba has not been included or sufficiently represented. Hence, there is a need for a study that offers an overview of the presence of dentists exiled in Latin America, focusing on Cuba and particularly, on Luís Amado Blanco Fernández, a personality who has been studied from a literary point of view (as a poet, novelist, playwright, literary and theater critic), but not for his work as a dentist and his contributions to Cuban dentistry, nor has been studied his work as a diplomat in depth.